2020
DOI: 10.14202/vetworld.2020.2156-2165
|View full text |Cite
|
Sign up to set email alerts
|

Multidrug-resistant Escherichia coli and Salmonella spp. isolated from pigeons

Abstract: Background and Aim: Pigeon rearing has been gaining popularity for recent years. They are reared remarkably very close to the house of the owner. This activity, therefore, may pose potential threats for humans as well as other animals as pigeons may carry and spread different pathogens including drug-resistant bacteria. This study was conducted to explore the prevalence of Escherichia coli and Salmonella spp. as well as their antibiogram profile along with an association analysis. Materials and Methods: Forty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…At the same time, Elgohary et al [43] recorded a resistant of salmonella isolates to doxycycline. The current Salmonella isolates classified as multidrug resistant (MDR) with highest resistance to rifampicin and erythromycin (91.7% and 83.4%) followed by chloramphenicol and ampicillin (58.4% and 58.3%); which agreed with that previously reported by Abulreesh [7] and Hosain, et al [51] and disagreed with Karim et al [34] who reported resistant of salmonella isolates to erythromycin (19.05%). In contrast, results by Yousef and Mamdouh [52] and AS and Shalaby [47] revealed high sensitivity of salmonella isolates from pigeons to ampicillin, which disagreed with our antibiogram assay to ampicillin.…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…At the same time, Elgohary et al [43] recorded a resistant of salmonella isolates to doxycycline. The current Salmonella isolates classified as multidrug resistant (MDR) with highest resistance to rifampicin and erythromycin (91.7% and 83.4%) followed by chloramphenicol and ampicillin (58.4% and 58.3%); which agreed with that previously reported by Abulreesh [7] and Hosain, et al [51] and disagreed with Karim et al [34] who reported resistant of salmonella isolates to erythromycin (19.05%). In contrast, results by Yousef and Mamdouh [52] and AS and Shalaby [47] revealed high sensitivity of salmonella isolates from pigeons to ampicillin, which disagreed with our antibiogram assay to ampicillin.…”
Section: Discussionsupporting
confidence: 77%
“…Our results run parallel with those recorded in; Dakahlia Governorate (6.7%, 2/30) by Abd El-Tawab et al [30], in Giza governorate (5%, 10/200) by Ahmed [28]. Moreover, Adesiyun et al [31], Dovč et al [32] and Methner and Lauterbach [33] isolated salmonella from pigeon cloacal swabs with percentages of 5, 5.7 and 7.04 respectively and less than that obtained by Abdeen et al [29] and Karim et al [34] who isolated salmonella from pigeons as 20% in Menoufiya Governorate. Also, Nabil and Younis [35] detected salmonella spp in 17% of pigeons collected from different governorates, where the isolation rate was (17.24%, 5/29) in Dakahlia, (17.39%, 4/23) in Damietta, (15%, 3/20) in Gharbia, (15.38%, 2/13) in Kafr ElSheik and (20%, 3/15) in Sharika Governorates But, lower rate of salmonella isolation was recorded as 2% only in the examined free-living pigeons in Makkah region, Saudi Arabia by Abulreesh [7] and as 1.5% in north England in the examined pigeon samples by Hughes et al [36].…”
Section: Discussionmentioning
confidence: 98%
“…Various degrees of resistance found against NA have been reported in Salmonella in Bangladesh. About 20% to 100% resistance found in Salmonella to NA secluded from poultry and environmental samples at a different region of Bangladesh [23][24][25]32,40,43,45,47]. Early, Nikolić et al [90] observed 95.50% resistance of Salmonella to NA in broiler isolates in Serbia.…”
Section: Resistance To Fluroquinolonesmentioning
confidence: 99%
“…Azithromycin is an azalide, a sort of macrolide antibiotic. Salmonella in Bangladeshi poultry has been found to have varying degrees of azithromycin resistance, ranging from 18.18% to 81.25% [25,26,[33][34][35]39,40,48]. Last year, Tîrziu et al [93] also reported 88.20% resistance in Salmonella to azithromycin was isolated from store raw poultry in Romania.…”
Section: Resistance To Macrolidesmentioning
confidence: 99%
See 1 more Smart Citation